Characterisations of Kraft Pulp and Paper Properties from Acacia Auriculiformis A. Cunn. Ex Benth.- A Confocal Microscopy Analysis - Liew, Kang Chiang (2001)
This study was carried out to characterise the transverse dimensions of mechanically treated (beaten) kraft Acacia auriculiformis pulp (AAP) and mixed tropical hardwood commercial pulp (MTHCP) fibres using the fast and non-destructive method of optical sectioning ability of confocal laser scanning microscopy. Also included in the study are the determination of chemical constituents, fibre morphologies using the image analyser and the optimum pulping conditions. Laboratory handsheets were produced using pulps beaten at varying beating degrees using the PFI mill, and evaluated for their physical and mechanical properties. Established standards were followed throughout the study. Results from the chemical constituents and fibre morphology determinations for A. auriculiformis sample were within the comparable range of previous studies. Optimum kraft pulping conditions was achieved at 19% active alkali for A. auriculiformis wood chips with a 51.9% screened yield, 0.085% reject and Kappa number 19.1. Laboratory handsheets were produced from AAP and MTHCP fibres that were beaten using the PFI mill, at 3 beating degrees; 0, 5000 and 10000 revolutions. Generally, the AAP fibres exhibited comparable, if not better, physical and mechanical properties than MTHCP. As beating progressed, pulp freeness decreased with increasing drainage time. This has resulted the tensile strength, bursting strength, tearing resistance, and folding endurance to increase but an inverse for bulk and air permeance.